Development of Internet of Things (IoT) Enabled Device for Environmental Control In Livestock Structures (2024)
Ventilation plays a critical role in maintaining optimal condition^ for livestock health and productivity. The deployment of smart technologies is gainf g ascendancy in 21st century agriculture and through the deployment of sensors and Internet of Things (IoT) technology, the efficiency and sustainability of livestock production sy wm in Nigeria can be improved, ultimately benefiting both farmers and animals. This project was carried out to develop an IoT- enabled device for the ventilation of livestock structures. This made it possible to collect real-time data on temperature, humidity, and air quality within the livestock structures, thereby enabling farmers to make informed decisions about ventilation adjustments. Data collected by IoT sensors can also be stored and analyzed on cloud-based platforms, providing farmers with historical trends and insights; information which can be valuaJe for making informed decisions. The device was tested at the University of Ibadan Teaching and Research farm, and the performance was satisfactory. In order improve the management of livestock, farmers are advised to deploy such systems to monitor and control the ventilation system remotely, and in real-time.